Resource Support Strategy dalam Pengelolaan Destinasi Wisata Kelor Berbasis Edukasi - Rahman, Sindi Arista; Arifin, Syamsul; Isdiantoni, Isdiantoni; Santosa, Ribut; Rasaili, Wilda (Universitas Galuh, 2024)
Poteran Village is the island with the largest moringa producer in Sumenep Regency. The results of the Moringa plant are then processed into various food products such as Moringa noodles, Moringa tea, Moringa flour and Moringa capsules. Based on this potential, it is important to develop it into a tourist destination based on educational tourism with an empowerment management strategy. As is known, Moringa tourism studies have not received much attention from academics. Therefore, research was conducted to find out how Moringa can be managed as a culinary tourism attraction based on educational tourism using resource strategies. The research uses a qualitative method with focus group discussion as a data collection method. The results of this research show 1) readiness of facilities as the responsibility of stakeholders, 2) Optimization of human resource empowerment related to community empowerment as the main actor, 3) Utilization of financial resources as the main driver in launching the Moringa educational tourism development program, 4) institutional strategy is a strategy that used in order to seek the role of institutions in developing education-based Moringa tourism destinations.